The developmental effects of low-level procymidone towards zebrafish embryos and involved mechanism. (February 2018) - Wu, Yuqiong; Zuo, Zhenghong; Chen, Meng; Zhou, Yixi; Yang, Qihong; Zhuang, Shanshan; Wang, Chonggang
Abstract: Procymidone (PCM), a dicarboximide fungicide, is widely used in agriculture to control plant diseases. In the present study, zebrafish embryos were exposed to PCM at 0, 10, 100 and 1000 ng/L for 72 h, the development and cardiac functioning of larvae were observed and determined. The results showed that hatching rate was significantly decreased in the 1000 ng/L treatment, and pericardial edema rate and spine curvature rate were significantly increased in the 100 and 1000 ng/L groups. The PCM-treated larvae exhibited an increased heart rate as well as arrhythmia, and shortened low jaw. The transcription levels of cardiac development-related genes tbx5, nkx2.5, tnnt2, gata4, myh6, myl7, cdh2, ryr2 were altered, which might be responsible for the cardiac developmental and functioning defects in the larvae. The deformation in bone development might be related with the impaired transcription levels of ihh, shh, bmp2b, bmp4, gh, igf1, sox9, gli2 . The activities of Na + /K + -ATPase and Ca 2+ -ATPase were significantly inhibited by 100 ng/L and 1000 ng/L PCM exposure, which might be a cause for the occurrence of pericardial edema and skeletal deformation. The results of this study will be helpful in evaluating the potential threat of PCM to fish population in the aquatic environment. Highlights: Exposure to PCM increased pericardial edema rate and spine curvature rate. PCM exposure resulted in cardiac and skeletal defects. PCM exposure altered the transcription of genes related to cardiac and skeletal development. The activities of Na +, K + -ATPase and Ca 2+ -ATPase were inhibited.